Advanced electrotechnology for marine engineers - Lavers, Christopher Ralph (Adlard Coles Nautical, 2014)
"This book is a companion to Reeds Vol. 6: Basic Electrotechnology for Marine Engineers and covers aspects of theory beyond the scope of Volume 6. The book will cover the more advanced topics in electrotechnology for professional trainees studying Merchant Navy Marine Engineering Certificates of Competency (CoC) as well as the syllabi in electrotechnology for undergraduates studying for BSc, BEng and MEng degrees in marine engineering and electrical engineering. The new edition will provide worked examples and test exam questions, corresponding to current Merchant Navy Qualifications. Other revisions will include new material on emerging technology areas such as image intensifiers (photoelectric effect, secondary emission), thermal imaging cameras, radar, increased maritime use of LEDs, various semiconductor physics devices including the laser, as well as discussions of binary or digital theory"--Abstract
Keywords: Electrical engineering.; Electrical engineering -- Problems, exercises, etc.; Marine engineering.; Marine engineering -- Problems, exercises, etc.; elektronické knihy; electronic books